ANALISIS MAJAS PERBANDINGAN DALAM PUISI “ROCK CLIMBING” KARYA JUNIARSO RIDWAN - Fatimah Insanul Hakim; Riana Dwi Lestari; Ika Mustika (IKIP Siliwangi, 2020)
The use of figure of speech in poetry is very important, because poetry is a work that contains beauty. Language style in poetry makes language in poetry different from literature in general. This research was conducted with the aim of knowing what comparative figures are contained in one of Juniarso Ridwan's poems entitled